Reducing mobile bearing dislocations in the Oxford Domed Lateral unicompartmental knee replacement implant - Yang, I (2022)
The Oxford Domed Lateral (ODL) mobile bearing Unicompartmental Knee Replacement (UKR) provides good clinical results, but the bearing dislocation rate is unacceptably high.